2020
DOI: 10.3390/app10155311
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study of Strata Movement Behavior in Mining a Longwall Top Coal Caving Panel of a Composite Coal Seam with Partings

Abstract: Strata movement due to extraction of a longwall panel is of great significance both in terms of environment and ground control. Thick coal seam extraction is expected to severely disturb the overburden, which is critical. Most studies use only one or two methods to investigate strata movement that are not thorough or comprehensive. This paper presents a detailed comprehensive case study of strata movement in extraction of a longwall top coal caving panel of a composite coal seam with partings in the Baozigou C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Авторами предлагается новая методика исследования процессов деформирования на физической модели, основанная на решении «обратной» задачи воспроизведения заданной эволюции процессов сдвижения земной поверхности по данным натурных реперов и экстраполяции этих процессов при сохранении темпов прироста вертикальных оседаний земной поверхности, обусловленных процессами деформирования и разрушения целиков [28][29][30].…”
Section: методика и результаты исследованийunclassified
“…Авторами предлагается новая методика исследования процессов деформирования на физической модели, основанная на решении «обратной» задачи воспроизведения заданной эволюции процессов сдвижения земной поверхности по данным натурных реперов и экстраполяции этих процессов при сохранении темпов прироста вертикальных оседаний земной поверхности, обусловленных процессами деформирования и разрушения целиков [28][29][30].…”
Section: методика и результаты исследованийunclassified
“…Известно, что в основе метода моделирования на ЭМ лежит разработка ЭМ, удовлетворяющих критериям подобия [5,6,[24][25][26][27][28][29]. Среди последних необходимо выбрать те из них, которые наиболее важны для характера исследуемых процессов.…”
Section: общая методология физического моделирования на эквивалентных...unclassified
“…Such research has enriched the theoretical system of surrounding rock control. Furthermore, scholars have used different experimental and numerical methods to collate a large number of field application cases [16][17][18][19][20]; this is also expected to serve as a reference for future research in this field. Researchers have reported that the principal stress has a significant influence on the stability of roadway surrounding rocks [21][22][23][24].…”
Section: Engineering Backgroundmentioning
confidence: 99%